Generation of collision-induced Early to Middle Miocene adakitic magmas in Pertek (Tunceli) area from Eastern Anatolia postsubductional setting, Turkey - Kurum, Sevcan; coban, Hakan; Aydin, Pinar (Tubitak Scientific & Technological Research Council Turkey, 2021)
Early to Middle Miocene andesite-dacite porphyries are well exposed to the Pertek area of Tunceli, Eastern Anatolia, and represent an example of adakite-like magma generation in Eastern Anatolia (postsubductional) collisional setting. Mineral associations in these porphyries are composed of plagioclase (oligoclase-andesine-labradorite), amphibole (pargasite-ferropargasite), biotite, rare quartz, K-feldspar, and minor Fe-Ti oxides. Geochemically they are high-K calc-alkaline in nature and characterized by high SiO2 ( 62 wt.%), Al2O3 (mostly >16 wt.%), Na2O/K2O ratio (1.3-1.7), and Sr (generally >400 ppm) contents. Volcanic rocks display depletion in HFSEs, Nb, Ta, and Ti, and slight negative Eu anomaly; have low HREEs, Y (<11 ppm) and Yb (<0.75 ppm) contents, and are enriched in LREE, LILE, Zr, and Hf. These geochemical traits point to the adakite-like affinity for Pertek andesite-dacite porphyries, however, they present some geochemical characteristics of both oceanic slab-derived and continental crust-derived adakites and show a dual character. Enrichment in K2O, Th, Rb, and Hf in these adakitic porphyries is mostly associated with the crust-derived terrigenous sediments during active subduction, before the Early Miocene. It is concluded that the continent-continent collision between the Arabian Plate and Eurasian Plate, break-off of Bitlis slab, and the onset of volcanism in the region was developed at Early to Middle Miocene, and the Pertek adakitic volcanism was triggered by collision-and slab break-off-induced asthenospheric mantle flows. Accordingly, our results show that a mixture of varying amounts of melts fed by sources from both amphibolitic lower crust, and subcontinental lithospheric mantle metasomatized by sediment fluids is the most likely parental magma to the Pertek adakitic porphyries.
Keywords: Adakitic porphyries; hybrid source; continental collision; slab break-off; mantle flow; Pertek-Tunceli-Elazig; Eastern Anatolia